2017
DOI: 10.1016/j.quaint.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene history of woodland dynamics and wood use in an ancient mining area of the Pyrenees (Ariège, France)

Abstract: This paper focuses on past woodland changes and land uses in an ancient mining area of the Eastern Pyrenees (Ari ege, France). The area discussed is located at the western entrance of the Vicdessos, a valley with significant steel production, and it is crossed by the road used from the 14th c. to the end of the 18th c. for the iron-charcoal exchange with the forest Province of Couserans. The introduction of this singular exchange and the silver ore mining history of this border area raise the question of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…The relevance of using charcoal from both sources has been also demonstrated by another study carried out on an ancient mining area, Argentières, Aulus-les-bains, in the French Pyrenees, not far from our study area (Fig. 1b;Py-Saragaglia et al 2017). In this study, the small input of charcoal from kiln sites to soil charcoal found in pits is supported by their low charcoal content, close to that observed at the tree-line, and the proportions of main taxa that clearly differ between pedoanthracological pits and the nearest charcoal kilns.…”
Section: Relevance Of Applying Pedoanthracology To An Ancient Charcoasupporting
confidence: 76%
See 3 more Smart Citations
“…The relevance of using charcoal from both sources has been also demonstrated by another study carried out on an ancient mining area, Argentières, Aulus-les-bains, in the French Pyrenees, not far from our study area (Fig. 1b;Py-Saragaglia et al 2017). In this study, the small input of charcoal from kiln sites to soil charcoal found in pits is supported by their low charcoal content, close to that observed at the tree-line, and the proportions of main taxa that clearly differ between pedoanthracological pits and the nearest charcoal kilns.…”
Section: Relevance Of Applying Pedoanthracology To An Ancient Charcoasupporting
confidence: 76%
“…(fir) are the most widely reported changes in the northern Pyrenees (Kenla 1977;Jalut 1984;Galop and Jalut 1994;Galop et al 2003). Since Gallo-Roman times (between the 1st century BC and the 4th-5th century AD), and especially from the end of the medieval period (ca AD 1500), mining and metallurgical processes are known to have caused further changes in woodland distribution, structure and composition (Camarero et al 1998;Davasse 2000;Dubois and Métailié 2001;Rius et al 2012;Py-Saragaglia et al 2017). But from these data, it remains difficult to accurately characterise these processes with high spatial resolution, which are very variable from one upper valley to another (Galop and Jalut 1994).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of charcoal remains enables one to identify the tree species used for charcoal burning in order to study the exploitation of the forest and the impact of charcoal production on soil properties (e.g. Nelle 2003, Deforce et al 2013, Knapp et al 2015, Dupin et al 2017, Hazell et al 2017, Ludemann et al 2017, Py-Saragaglia et al 2017. Research on charcoal hearth remains and historical charcoal burning has also been carried out in Poland (Rutkiewicz et al 2019).…”
Section: Introductionmentioning
confidence: 99%